2015
DOI: 10.1142/s0219720015400090
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-based prediction of transcription upregulation by auxin in plants

Abstract: Auxin is one of the main regulators of growth and development in plants. Prediction of auxin response based on gene sequence is of high importance. We found the TGTCNC consensus of 111 known natural and artificially mutated auxin response elements (AuxREs) with measured auxin-caused relative increase in genes' transcription levels, so-called either "a response to auxin" or "an auxin response." This consensus was identical to the most cited AuxRE motif. Also, we found several DNA sequence features that correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
1
7
0
1
Order By: Relevance
“…Additionally, we compiled a set of SNPs in the TBP-binding sites associated with human diseases [ 54 ], including the AIDS pandemic [ 55 ], and with commercially important traits of plants and animals [ 56 ]. Then, we confirmed the three-step predictions by means of these SNPs [ 57 ] and by means of transcriptomes of the human brain [ 58 ], the auxin response in plants [ 59 , 60 ], and the data from 68 independent experiments (for review, see [ 61 ]). To finalize this comprehensive verification of the three-step model of TBP binding to a promoter [ 47 , 49 ], we created a freely available Web service [ 62 ] for users who wish to apply this bioinformatics application to data on the TBP/promoter-complexes in humans: http://beehive.bionet.nsc.ru/cgi-bin/mgs/tatascan/start.pl .…”
Section: Introductionsupporting
confidence: 57%
“…Additionally, we compiled a set of SNPs in the TBP-binding sites associated with human diseases [ 54 ], including the AIDS pandemic [ 55 ], and with commercially important traits of plants and animals [ 56 ]. Then, we confirmed the three-step predictions by means of these SNPs [ 57 ] and by means of transcriptomes of the human brain [ 58 ], the auxin response in plants [ 59 , 60 ], and the data from 68 independent experiments (for review, see [ 61 ]). To finalize this comprehensive verification of the three-step model of TBP binding to a promoter [ 47 , 49 ], we created a freely available Web service [ 62 ] for users who wish to apply this bioinformatics application to data on the TBP/promoter-complexes in humans: http://beehive.bionet.nsc.ru/cgi-bin/mgs/tatascan/start.pl .…”
Section: Introductionsupporting
confidence: 57%
“…In Arabidopsis, AtWOX11 and AtWOX12, orthologs of rice WOX6 and WOX11, respectively, are reported to play roles in root development (Liu et al, 2014;Hu and Xu, 2016;Sheng et al, 2017). We found that both WOX6 and WOX11 contain auxin response elements, TGTCNC (Ponomarenko and Ponomarenko, 2015), in their promoter regions (Supplemental Figure 9). We further verified that WOX6 and WOX11 were not only responsive to NAA treatment, but also displayed an asymmetrical expression pattern like that of IAA20 during shoot gravitropism under light ( Figures 6C and 6D).…”
Section: Wox6 and Wox11 Are Downstream Targets Of Auxin In Determininmentioning
confidence: 81%
“…This refined auxin‐responsive motif was more predictive of auxin responsiveness compared with using the canonical DR5 motif within the first 500 bp of the promoter sequence; however, it has not been functionally tested in vivo . Modelling of auxin responses based on promoter motifs is not only powerful in confirming known AuxREs, but correlations using 111 natural or artificially tested AuxREs showed a positive correlation between auxin inducibility and the abundance of five trinucleotides and five β ‐helical DNA features around these known AuxREs, confirming that in addition to ARF sequence specificity, TATA‐binding protein affinity for DNA and nucleosomal packing is also important in modelling auxin response at the promoter level (Ponomarenko & Ponomarenko ). Enigmatically, many auxin‐regulated genes lack AuxREs in their promoters (Goda et al .…”
Section: Auxin Response Factor Target Sequences and Binding Specificitymentioning
confidence: 99%